Marketing empresarial y su incidencia en la participación del mercado de la cooperativa juventud ecuatoriana progresista ltda. agencia Santo Domingo, año 2020. estrategias de marketing. - Cepeda Navarrete, Zulay Adriana (2021)
Currently, the Cooperativa de Ahorro y Crédito Juventud Ecuatoriana Progresista Ltda. (JEP), Santo Domingo agency, operates with a limited advertising management capacity, to offer and promote its financial products, which are offered to its clients; Many of them are business owners that have been affected by the health emergency caused by COVID-19 and urgently need to recapitalize to restart their business operations again. For this reason, the general objective of the research is to evaluate the impact of business marketing on the market share of the Cooperativa Juventud Ecuatoriana Progresista Ltda., Agency, Santo Domingo, year 2020. On the other hand, the research methodology that It was used a mixed approach, applying methods that allowed to substantiate the findings of the study phenomenon, an exploratory research and field research was used; Primary information was collected through an online survey, addressed to users of the Financial System of Savings and Credit Cooperatives of the Santo Domingo canton, in order to fully understand the general environment of the JEP Cooperative. Finally, according to the results obtained for the research, business marketing strategies have been proposed to increase the participation of the clients of the Cooperativa de Ahorro y Crédito Juventud Ecuatoriana Progresista Ltda., Santo Domingo agency, year 2021, in addition it is intended improve the positioning of the brand, through the execution of three types of advertising strategies. Keywords: Business Marketing, Business Strategies, Market.